Nexus between green bonds, financial and environmental indicators - Hung, Ngo Thai (Economics and Business Letters, 2021)
This study uses a novel perspective to examine the causal connectedness between green bonds and other conventional assets, including clean energy, price of CO2 emission allowances, Bitcoin, and the S&P 500 stock market covering from January 2013 to March 2019. We apply the Multilayer Perceptron Neural Network Non-linear Granger causality and Transfer Entropy to detect possible changes in the causal direction between green bonds and other considered variables. We find a bidirectional relationship between green bonds, S&P 500, and Bitcoin markets, while green bonds have a unidirectional connection with the price of CO2 emission allowances.